The relationship between cannabis involvement and suicidal thoughts and behaviors. (1st May 2015) - Delforterie, M.J.; Lynskey, M.T.; Huizink, A.C.; Creemers, H.E.; Grant, J.D.; Few, L.R.; Glowinski, A.L.; Statham, D.J.; Trull, T.J.; Bucholz, K.K.; Madden, P.A.F.; Martin, N.G.; et al.
Highlights: We studied the relation of cannabis involvement with suicidal thoughts and behaviors. Cannabis involvement was related to suicidal ideation, albeit modestly. Cannabis involvement was also related to unplanned suicide attempts, albeit modestly. Strongest evidence for association, even after adjustment, was with cannabis problems. Cannabis involvement was not related to suicide planning or planned attempts. Abstract: Background: In the present study, we examined the relationship between cannabis involvement and suicidal ideation (SI), plan and attempt, differentiating the latter into planned and unplanned attempt, taking into account other substance involvement and psychopathology. Methods: We used two community-based twin samples from the Australian Twin Registry, including 9583 individuals (58.5% female, aged between 27 and 40). The Semi-Structured Assessment of the Genetics of Alcoholism (SSAGA) was used to assess cannabis involvement which was categorized into: (0) no cannabis use (reference category); (1) cannabis use only; (2) 1–2 cannabis use disorder symptoms; (3) 3 or more symptoms. Separate multinomial logistic regression analyses were conducted for SI and suicide attempt with or without a plan. Twin analyses examined the genetic overlap between cannabis involvement and SI. Results: All levels of cannabis involvement were related to SI, regardless of duration (odds ratios [ORs] = 1.28–2.00, p < 0.01). Cannabis use and endorsing ≥3 symptoms were associated with unplanned (SANP; ORs = 1.95 and 2.51 respectively, p < 0.05), but not planned suicide attempts ( p > 0.10). Associations persisted even after controlling for other psychiatric disorders and substance involvement. Overlapping genetic ( rG = 0.45) and environmental ( rE = 0.21) factors were responsible for the covariance between cannabis involvement and SI. Conclusions: Cannabis involvement is associated, albeit modestly, with SI and unplanned suicide attempts. Such attempts are difficult to prevent and their association with cannabis use and cannabis use disorder symptoms requires further study, including in different samples and with additional attention to confounders.